The Ixodes ricinus salivary gland proteome during feeding and B. Afzelii infection: New avenues for an anti-tick vaccine. Issue 12 (17th March 2023) - Klouwens, Michelle J.; Trentelman, Jos J.A.; Barriales, Diego; Ersoz, Jasmin I.; Azkargorta, Mikel; Elortza, Felix; Šíma, Radek; Hajdušek, Ondrej; Lavin, José-Luis; Tomás Cortazar, Julen; Escobes Corcuera, Iraide; Colstrup, Emil; et al.
Abstract: Introduction: Borrelia burgdorferi sensu lato, the causative agents of Lyme borreliosis, are transmitted by Ixodes ticks. Tick saliva proteins are instrumental for survival of both the vector and spirochete and have been investigated as targets for vaccine targeting the vector. In Europe, the main vector for Lyme borreliosis is Ixodes ricinus, which predominantly transmits Borrelia afzelii . We here investigated the differential production of I. ricinus tick saliva proteins in response to feeding and B. afzelii infection. Method: Label-free Quantitative Proteomics and Progenesis QI software was used to identify, compare, and select tick salivary gland proteins differentially produced during tick feeding and in response to B. afzelii infection. Tick saliva proteins were selected for validation, recombinantly expressed and used in both mouse and guinea pig vaccination and tick-challenge studies. Results: We identified 870 I. ricinus proteins from which 68 were overrepresented upon 24-hours of feeding and B. afzelii infection. Selected tick proteins were successfully validated by confirming their expression at the RNA and native protein level in independent tick pools. When used in a recombinant vaccine formulation, these tick proteins significantly reduced the post-engorgement weights of I. ricinus nymphs in two experimental animal models. Despite the reduced ability of ticks to feed on vaccinated animals, we observed efficient transmission of B. afzelii to the murine host. Conclusion: Using quantitative proteomics, we identified differential protein production in I. ricinus salivary glands in response to B. afzelii infection and different feeding conditions. These results provide novel insights into the process of I. ricinus feeding and B. afzelii transmission and revealed novel candidates for an anti-tick vaccine.